The effect of thermocycling on the degree of conversion and mechanical properties of a microhybrid dental resin composite - Ghavami-Lahiji, Mehrsima (Restor Dent Endod, 2018)
OBJECTIVE: The purpose of this study was to investigate the degree of conversion (DC) and mechanical properties of a microhybrid Filtek Z250 (3M ESPE) resin composite after aging. METHOD: The specimens were fabricated using circular molds to investigate Vickers microhardness (Vickers hardness number [VHN]) and DC, and were prepared according to ISO 4049 for flexural strength testing. The initial DC (%) of discs was recorded using attenuated total reflectance-Fourier transforming infrared spectroscopy. The initial VHN of the specimens was measured using a microhardness tester under a load of 300 g for 15 seconds and the flexural strength test was carried out with a universal testing machine (crosshead speed, 0.5 mm/min). The specimens were then subjected to thermocycling in 5°C and 55°C water baths. Properties were assessed after 1,000–10,000 cycles of thermocycling. The surfaces were evaluated using scanning electron microscopy (SEM). Data were analyzed using 1-way analysis of variance followed by the Tukey honest significant difference post hoc test. RESULTS: Statistical analysis showed that DC tended to increase up to 4,000 cycles, with no significant changes. VHN and flexural strength values significantly decreased upon thermal cycling when compared to baseline (p < 0.05). However, there was no significant difference between initial and post-thermocycling VHN results at 1,000 cycles. SEM images after aging showed deteriorative changes in the resin composite surfaces. CONCLUSIONS: The Z250 microhybrid resin composite showed reduced surface microhardness and flexural strength and increased DC after thermocycling.